Elaboración del sistema contable en la plantación dreams flowers l.c. del sector Pupana Norte de la parroquia Guaytacama en el año 2014 - Cazco Hurtado, Martha Cristina (2015)
This research was conducted in the plantation Dreams Flowers in the North Sector Pupana Guaytacama Parish of Latacunga Canton; with the collaboration of the manager of the company. The goal of the research is to understand the management of the entire accounting process, In the research conducted, it is identified that the main problem is the weakness of the management of accounting documents and the lack of accounting processes that are indispensable for the recording of revenues, expenses, inventory, accounts payable, and receivables, among others….